Genome-wide QTL mapping for stripe rust resistance in spring wheat line PI 660122 using the Wheat 15K SNP array - Yan, Qiong; Jia, Guoyun; Tan, Wenjing; Tian, Ran; Zheng, Xiaochen; Feng, Junming; Luo, Xiaoqin; Si, Binfan; Li, Xin; Huang, Kebing; Wang, Meinan; Chen, Xianming; et al. (Frontiers in Plant Science, 2023)
Stripe rust is a global disease of wheat. Identification of new resistance genes is key to develop and grow resistant varieties for control of the disease. Wheat line PI 660122 has exhibited a high level of stripe rust resistance for over a decade. However, the genetics of stripe rust resistance in this line has not been studied.A set of 239 recombinant inbred lines (RILs) was developed from a cross between PI 660122 and an elite Chinese cultivar Zhengmai 9023. The RIL population was phenotyped for stripe rust response in three field environments and genotyped with the Wheat 15K single nucleotide polymorphism (SNP) array. A total of 9 quantitative trait loci (QTL) for stripe rust resistance were mapped to chromosomes 1B (1 QTL), 2B (1), 4B (2 QTL), 4D (2), 6A (1), 6D (1), and 7D (1), of which 7 QTL were stable and designated